Professional Competency Requirements for Maintenance and Operation of Power Battery Systems - Wang, Wei; Hu, Zan; Qi, Pei; Li, Xiaopeng (International Journal of Natural Resources and Environmental Studies, 2024)
The power battery system is one of the high-risk components for new energy vehicles, and standardized operation and maintenance is one of the effective measures to improve the safety of new energy vehicles. The operation and maintenance of the power battery system includes daily operation, first level maintenance, and second level maintenance. A combination of practical research and theoretical analysis is adopted to confirm different maintenance tasks, job contents, and technical requirements, in order to improve the standardization and safety of operations. Fault mode analysis is a continuation of fault maintenance and provides practical basis for the design and process improvement of power battery systems.